2006
DOI: 10.2174/138527206777698057
|View full text |Cite
|
Sign up to set email alerts
|

Candida rugosa Lipase: A Traditional and Complex Biocatalyst

Abstract: Different commercial preparations from Candida rugosa lipase lead often to an irreproducible behaviour when employed in slightly hydrated media, even when different samples from the same supplier are used. This conduct is triggered by several causes, such as the different concentration of the "real" catalyst in the different crude samples (quantity), or the inherent problems related to heterogeneous biocatalysts (i. e., different amount of water, diffusional problems, etc); furthermore, for C. rugosa lipase, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The density of the PMMA is taken as 1.19 g/cm 3 . By using the reported molecular weight and diameter of C. rugosa lipase, which are 60 kDa and 6.8 nm, respectively [21], the curve in Fig. 6 depicts calculations of the loading of lipase on PMMA nanofibers.…”
Section: Enzyme Immobilizationmentioning
confidence: 99%
“…The density of the PMMA is taken as 1.19 g/cm 3 . By using the reported molecular weight and diameter of C. rugosa lipase, which are 60 kDa and 6.8 nm, respectively [21], the curve in Fig. 6 depicts calculations of the loading of lipase on PMMA nanofibers.…”
Section: Enzyme Immobilizationmentioning
confidence: 99%
“…The new enzymes used in this paper are the lipase A from C. antarctica (CALA) and the commercial lipase from Candida rugosa (CRL). Both enzymes have a proper lid and have been used in many different applications [46][47][48][49][50], After characterizing the biocatalyst, we have studied the possibilities of applying the strategy of unfolding/refolding to these biocatalysts. To our knowledge, this is the first report of reactivation of any CALA or CRL immobilized preparations.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical synthesis of DAP was first developed by oxidation of o-phenylenediamine (OP) using ferric chloride in the 1870s [3]. Later, Tarcha et al [4] reported that enzyme (biochemical)-catalyzed oxidation of OP could also yield DAP as an alternative way.…”
Section: Introductionmentioning
confidence: 99%